Love in Theravada Buddhism Approach - Dhammarato, Phra Piyapong (Journal of Dhamma for Life, 2022)
This academic article aims to present love according to Theravada Buddhism. In human existence, love is very powerful and can be expressed both negatively and positively in Buddhism. That love and Buddhism are inseparable between Buddhism and Buddhists. Love in Buddhism is universal love. Love in Buddhism is implemented according to the way in human society, which is kindness, good-will, and compassion. See everyone as your friend and don’t want anything in return. Which is the love that is equal among all beings. Love in the Buddhist viewpoint means kindness, a person’s goodwill toward others, compassion, and understanding. The interest or desire to promote the principles concerning love and benefit to fellow human beings, which in this article presents 4 significant values, namely Sanheha, Pema, Metta, and Metta-apamanya.